The Role of Bmp- and Fgf Signaling Modulating Mouse Proepicardium Cell Fate - Garcia-Padilla, Carlos; Hernandez-Torres, Francisco; Lozano-Velasco, Estefania; Dueñas, Angel; Muñoz-Gallardo, Maria del Mar; Garcia-Valencia, Isabel S.; Palencia-Vincent, Lledó; Aranega, Amelia; Franco, Diego (Frontiers in Cell and Developmental Biology, 2022)
Bmp and Fgf signaling are widely involved in multiple aspects of embryonic development. More recently non coding RNAs, such as microRNAs have also been reported to play essential roles during embryonic development. We have previously demonstrated that microRNAs, i.e., miR-130, play an essential role modulating Bmp and Fgf signaling during early stages of cardiomyogenesis. More recently, we have also demonstrated that microRNAs are capable of modulating cell fate decision during proepicardial/septum transversum (PE/ST) development, since over-expression of miR-23 blocked while miR-125, miR-146, miR-223 and miR-195 enhanced PE/ST-derived cardiomyogenesis, respectively. Importantly, regulation of these microRNAs is distinct modulated by Bmp2 and Fgf2 administration in chicken. In this study, we aim to dissect the functional role of Bmp and Fgf signaling during mouse PE/ST development, their implication regulating post-transcriptional modulators such as microRNAs and their impact on lineage determination. Mouse PE/ST explants and epicardial/endocardial cell cultures were distinctly administrated Bmp and Fgf family members. qPCR analyses of distinct microRNAs, cardiomyogenic, fibrogenic differentiation markers as well as key elements directly epithelial to mesenchymal transition were evaluated. Our data demonstrate that neither Bmp2/Bmp4 nor Fgf2/Fgf8 signaling is capable of inducing cardiomyogenesis, fibrogenesis or inducing EMT in mouse PE/ST explants, yet deregulation of several microRNAs is observed, in contrast to previous findings in chicken PE/ST. RNAseq analyses in mouse PE/ST and embryonic epicardium identified novel Bmp and Fgf family members that might be involved in such cell fate differences, however, their implication on EMT induction and cardiomyogenic and/or fibrogenic differentiation is limited. Thus our data support the notion of species-specific differences regulating PE/ST cardiomyogenic lineage commitment.